Remplissage—when and how to fill in the defect - Idowu, Olumuyiwa; Chiu, Michael; Miller, John; Koh, Jason; Shi, Lewis (Annals of Joint, 2017)
Hill-Sachs lesions can be seen in 65–80% of initial glenohumeral dislocations, and up to 100% of recurrent instability episodes. Engaging Hills-Sachs lesions have been described as those that occur when the long axis of the humeral head defect is parallel to the anterior glenoid rim, allowing the humeral head defect to fall off of the glenoid fossa in essence becoming levered anteroinferiorly to the glenoid fossa. More recently, an arthroscopic technique, which involves soft tissue interposition into the humeral defect, known as remplissage (French: to fill in) procedure, has been developed to prevent Hill-Sachs lesion engagement on the glenoid rim. The purpose of this paper is to review the current literature surrounding the technique, indications, outcomes, and complications of this procedure.